MANAJEMEN PEMBELAJARAN BERBASIS FITRAH DI TPA SEKAR PURBALINGGA - Farah Nur Fadhilah; Novan Ardy Wiyani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study is intended to describe the nature-based learning management in TPA Sekar Purbalingga, so the scope of this research are: (1) nature-based learning planning activities; (2) activities of organizing learning based on nature; (3) nature-based learning implementation activities; and (4) nature-based learning supervision activities. This study uses a qualitative approach to the type of phenomenological research. Data were collected using interviews, observation and documentation. The data that has been collected is then analyzed using three stages, namely data reduction, data display and verification. The results showed that nature-based learning planning was carried out through the preparation of a curriculum that developed six programs, namely: a religious and moral value development program (NAM), a physical motor development program, a cognitive development program, a language development program, a social emotional development program, and an art development program. . Organizing natural-based learning is done by grouping children into classes based on their age. This is done because the nature of the child will develop is also influenced by the age factor. The implementation of nature-based learning is carried out through the development of the nature of faith, the development of the nature of learning, the development of the nature of talent, the development of the nature of sexuality, the development of the nature of aesthetics and language, the development of individual and social nature, and the development of physical nature. Play activities are carried out to develop the seven natures. Then in the supervision of nature-based learning, educational supervision activities are carried out aimed at fostering educators in carrying out their duties as organizers of nature-based learning.